Varying clinical features of Turkish Kawasaki disease patients - Gülhan, Bora; Kesici, Selman; Beken, Serdar; Çilsal, Erman; Kale, Gülsev; Alehan, Dursun; Kara, Ateş; Ozen, Seza (The Turkish Journal of Pediatrics, 2012)
Kawasaki disease (KD) is an acute, systemic and self-limited vasculitis that is complicated with the development of coronary artery (CA) aneurysms. We present the clinical features of Turkish KD patients from a tertiary referral center. When 33 KD patients were assessed, a number of features stood out as differing from the expected, for example, periungual peeling 7.5 +/- 7.5 days after fever onset–42.4% of patients had periungual peeling within 14 days after fever onset. CA involvement was detected at an average of 12.3 +/- 7.9 days after fever onset. Fifty percent of the patients had been diagnosed to have CA involvement within eight days after the onset of fever. The performance of criteria suggested by American Heart Association was satisfactory, with 19 of 29 patients (65.5%) having three or more of the required laboratory features (sensitivity 65.5%). We believe Turkish patients may present differences in the course of KD.